The ‘Pentol Bakar’ Application as an Innovative Approach in Mental Health Emergencies : A Scoping review - Ryka Widyaningtyas (NERS Jurnal Keperawatan, 2025)
The issue of mental health disorders is a complex problem that requires serious attention. The "Pentol Bakar" application was developed to evaluate Pentol Bakar as an innovation in patient pick-up services for mental health emergencies and to assess the strengths and weaknesses of the service, as well as to conduct a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis of the Pentol Bakar service for patients with mental health issues at RSJD Dr. Amino Gondohutomo. The literature search method in this study is a scoping review, involving searching for journals or research articles through search engines, then using the PCC framework to create inclusion and exclusion criteria for the journals. The process of article search and selection then used PRISMA-ScR. This review found a total of 893 articles, and the review results indicated that 5 articles were relevant to the research topic. The analysis showed that the "Pentol Bakar" application had some shortcomings for patients and/or their families, including limited exposure to and understanding of technology and the application, inadequate mobile phones for downloading the application, inability to pay for the service, and difficulty for healthcare workers in obtaining detailed information about the patient's condition. On the positive side, the application made it easier to handle psychiatric emergencies, provided broader access to services, and made hospital services more efficient. This study explores the outcomes related to psychiatric emergency handling, including the SWOT analysis. These findings are expected to contribute positively to improving the quality of mental health services at the relevant institution.